Serotonin 5-HT1A, 5-HT1B, and 5-HT2A receptor mRNA expression in subjects with major depression, bipolar disorder, and schizophrenia - López-Figueroa, Antonio L; Norton, Camille S; López-Figueroa, Manuel O; Armellini-Dodel, Denise; Burke, Sharon; Akil, Huda; López, Juan F; Watson, Stanley J (Biological psychiatry (1969), 2004)
Alterations of serotonin neurotransmission are implicated in both mood disorders and schizophrenia. Specific serotonin-receptor-based abnormalities in these psychiatric illnesses have been intensively studied; however, it has been difficult to draw any conclusions because of a lack of consensus. These inconsistencies have most likely arisen from the unavailability of selective ligands. Our study used in situ hybridization to quantify 5-HT(1A), 5-HT(1B), and 5-HT(2A) mRNA levels in the hippocampus (HC) and 5-HT(1A) and 5-HT(2A) mRNA levels in the dorsolateral prefrontal cortex (DLPFC) of subjects with a history of major depression disorder (MDD), bipolar disorder (BPD), schizophrenia, and a normal comparison group (15 subjects per group). In the DLPFC, there is a significant decrease in 5-HT(1A) mRNA of subjects with MDD and in 5-HT(2A) mRNA of subjects with BPD. Subjects with MDD have a significant decrease in 5-HT(1A) mRNA in the HC; subjects with BPD and schizophrenia had increased 5-HT(1B) mRNA levels and a significant decrease in 5-HT(2A) mRNA levels in the hippocampal formation. Alterations in 5-HT(1A,) 5-HT(1B), and 5-HT(2A) mRNA levels in the brains of subjects with both mood disorders and schizophrenia add further support for hypothesis of dysregulation of the serotonergic system in these psychiatric disorders.